Correction to: Agricultural trade policies and child nutrition in low- and middle-income countries: a cross-national analysis. - Adjaye-Gbewonyo, Kafui.; Vollmer, Sebastian.; Avendano, Mauricio.; Harttgen, Kenneth. (Tufts University. Tisch Library., 2019)
Springer Open.